2023
DOI: 10.1002/iid3.919
|View full text |Cite
|
Sign up to set email alerts
|

PABPC1 promotes cell proliferation and metastasis in pancreatic adenocarcinoma by regulating COL12A1 expression

Abstract: Background: The expression of cytoplasmic poly (A) binding protein-1 (PABPC1) has been reported in multiple cancer types. This protein is known to modulate cancer progression. However, the effects of PABPC1 expression in pancreatic adenocarcinoma (PAAD) have not been investigated. Here, we investigate the regulatory targets and molecular mechanisms of PABPC1 in PAAD. Methods: PABPC1 and collagen type XII α1 chain (COL12A1) expression in PAAD and their role in tumor prognosis and tumor stage were investigated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…PABPC1 promotes cell proliferation and metastasis by regulating COL12A1 expression in pancreatic adenocarcinoma. 33 Furthermore, PABPC1 expression is downregulated in several malignant gliomas, and therefore, it may be a predictor of preneural subtypes of gliomas; notably, in patients with glioma, high PABPC1 expression is significantly associated with a favorable prognosis. 34 In contrast, our risk model indicated that increased PABPC1 expression is associated with poor HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…PABPC1 promotes cell proliferation and metastasis by regulating COL12A1 expression in pancreatic adenocarcinoma. 33 Furthermore, PABPC1 expression is downregulated in several malignant gliomas, and therefore, it may be a predictor of preneural subtypes of gliomas; notably, in patients with glioma, high PABPC1 expression is significantly associated with a favorable prognosis. 34 In contrast, our risk model indicated that increased PABPC1 expression is associated with poor HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%